Use of billet scale as partial replacement of sand in concrete - Naganathan S.; Musazay J.A. (Building and Housing Research Center (BHRC), 2023)
This paper presents the results of an investigation done on the use of steel billet scale as partial replacement of sand in concrete. Concrete mixtures were made with various percentages of replacement of billet scale in lieu of sand. Tests were conducted on fresh concrete for slump and fresh density and on hardened concrete for compressive strength, ultrasonic pulse velocity (UPV), rebound number, and for durability of concrete by immersion in saline medium. It was found out that the concrete up to 15% replacement level of billet scale showed increase in performance than the control mixture. The concrete strength reduced relatively for those samples cured in saline medium, but the 15% replacement was still the optimum replacement proportion. Replacement level of less than 15% and as well as more than 15 % showed decrement in strength.